Penyesuaian Rencana Pembelajaran dan Penerapan Aturan Kelas Efektif Dalam Pengelolaan Kelas Daring - Masithoh Ekayani (Prosiding University Research Colloquium, 2021)
Education is necessary for the era's development. Knowledge and insight can get througheducation. School is one way to get a good education. A good school creates conducivelearning conditions for students. Conducive learning constructs through effective teachersas well. One indicator of an effective teacher is a teacher who has good classroommanagement skills. Classroom management is one of the challenges for teachers,especially in the current state of the COVID-19 virus pandemic. Learning activities turnedinto Distance Learning or online activities that were face-to-face learning. Strategies thatteachers could be done on online classes management are changing lesson plans and makeonline classes procedures. The creativity of teachers to use models, methods, learningmedia as well as give tasks and exercises in online classes is very important. The strictapplication of online classroom rules encourages students to focus and participating inonline learning. Implementation of online learning following the planning and enforcementof procedures can create effective online learning so that learning purposes could beachieved.